Celeng, Metafora Etika Politik Lingkungan:Inspirasi Prosa Lirik Perjalanan Celeng ke Surga, Karya F. Rahardi: Inspirasi Prosa Lirik Perjalanan Celeng ke Surga, Karya F. Rahardi - Dua, Mikhael; Sihotang, Kasdin (Respons: Jurnal Etika Sosial, 2024)
Politic is an inseparable part of human life. Politic is like a double-sided coin; it can be directed positively, meaning it is used to improve the welfare of society in accordance with its essence, or it can become a platform for conflict for power, awakening animalistic instincts through various cunning and dirty means to occupy certain positions. In its implementation, criticism of political life, especially the improper implementation of power, is always present. Such criticism is carried out in various ways. The method of literary writers is one such method. Writers convey criticism of bad power through the use of metaphors. Metaphorical instruments are diverse. One such method is using the name of an animal, the wild boar. Rahardi, a writer, demonstrates this in his book entitled "The Journey of Celeng To Heaven." In this book, Rahardi criticizes how those in power defend their interests using the diverse characters of regional wild boars. The metaphor of the wild boar is rich in meaning and contains a fundamental moral message. It addresses issues of justice, responsibility, concern, rationality, identity, and originality.